Characterization of PbS with different morphologies produced using a cyclic microwave radiation - Anukorn Phuruangrat (2018)
PbS was produced from different lead (Pb(CH3COO)2·H2O, PbCl2·2.5H2O, Pb(NO3)2) and sulfur (CH3CSNH2, CH5N3S, NH2CSNH2) sources in propylene glycol using a cyclic microwave radiation at different powers and prolonged times. PbS (cubic) was detected using X-ray diffraction (XRD) and selected area electron diffraction (SAED) techniques. The interpreted and simulated patterns are in good accord. Raman spectrometer revealed the presence of vibrations at 138, 273 and 439 cm-1. Different morphologies (nano-sized particles, hexapods, cubes, ferns and magic squares) were characterized using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). The product morphologies were influenced by the starting agents, microwave powers and prolonged times. © 2008 Elsevier B.V. All rights reserved.